A comparison of techniques used by lightweight and heavyweight judoists during the World and Olympic tournaments 1995-1999 - Sterkowicz, S.; Franchini, E. (2000)
The main results of the statistical analysis of the 4 813 actions were: 1.a predominance of Ashi-waza in both categories; 2. the best part of scores were obtained during the first three minutes of fight; 3. penalties accounted for almost half of the scores obtained; 4. we found a temporal trend in pattern of action scores, which was stronger in heavyweight categories. Percentage of Ippon, Waza-ari and Yuko decreased, whereas Hansokumake/Keikoku and Shido had a tendency to increase in the consecutive tournaments 1995 -1999; 5. some techniques that could not be classified according to the traditional system appeared in 1997.